PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PENALARAN MATEMATISPESERTA DIDIK DALAM PEMBELAJARAN MATEMATIKA KELAS VIII SMPN 1 2X11 ENAM LINGKUNG - Delvia Aulia Sukma (Jurnal Edukasi dan Penelitian Matematika, 2019)
Mathematical reasoning ability is a capability that is very much needed in mathematics. However, in the eighth grade of the junior high school 2x11 Enam Lingkung, the students' mathematical reasoning ability in mathematicalabiity was still in low level. The Problem Based Learning (PBL) model can be used to solve this problem. This study aimed to see the differences of the student’s mathematical reasoning ability between the student who learned mathematics by using Problem Based Learning and those who learned it directly. This research is a quasy-experimental research with static group design. The sample was taken by using simple random sampling. In which VIII C class was the experimental class while VIII D class become the control class. The instrument to assess the student’s reasoning ability was a final test in essay form. The findings showed that the student’s mathematical ability who studied mathematics by using Problem Based Learning were much better comparing to the students who studied the subject directly in the eighth grade of the junior high school 2x11 Enam Lingkung.Keywords- Mathematical Reasoning Ability, Problem Based Learning